Vastly different energy landscapes of the membrane insertions of monomeric gasdermin D and A3 - Viktoria Korn; Kristyna Pluhackova (Communications Chemistry)
Abstract Gasdermin D and gasdermin A3 belong to the same family of pore-forming proteins and executors of pyroptosis, a form of programmed cell death. To unveil the process of their pore formation, we examine the energy landscapes upon insertion of the gasdermin D and A3 monomers into a lipid bilayer by extensive atomistic molecular dynamics simulations. We reveal a lower free energy barrier of membrane insertion for gasdermin D than for gasdermin A3 and a preference of gasdermin D for the membrane-inserted and of gasdermin A3 for the membrane-adsorbed state, suggesting that gasdermin D first inserts and then oligomerizes while gasdermin A3 oligomerizes and then inserts. Gasdermin D stabilizes itself in the membrane by forming more salt bridges and pulling phosphatidylethanolamine lipids and more water into the membrane. Gasdermin-lipid interactions support the pore formation. Our findings suggest that both the gasdermin species and the lipid composition modulate gasdermin pore formation.